2011
DOI: 10.1002/hbm.21100
|View full text |Cite
|
Sign up to set email alerts
|

Invariance of firing rate and field potential dynamics to stimulus modulation rate in human auditory cortex

Abstract: The effect of stimulus modulation rate on the underlying neural activity in human auditory cortex is not clear. Human studies (using both invasive and noninvasive techniques) have demonstrated that at the population level, auditory cortex follows stimulus envelope. Here we examined the effect of stimulus modulation rate by using a rare opportunity to record both spiking activity and local field potentials (LFP) in auditory cortex of patients during repeated presentations of an audio-visual movie clip presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Interestingly, the tracking of the vocalization envelope becomes particularly salient when the phase-locked multi-unit responses are summed together. Given that synchronized ensembles of multi-unit activity are correlated with high gamma power of the LFPs [20][22], an intriguing possibility is that the high gamma activity that we report in this study is closely related to the multi-unit discharges recorded in animal primary auditory cortex during vocalization. Indeed, it has been found that the high gamma activity can be closely tied to neuronal discharge activity in human auditory cortex when subjects listen to naturalistic stimuli [20], [22].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, the tracking of the vocalization envelope becomes particularly salient when the phase-locked multi-unit responses are summed together. Given that synchronized ensembles of multi-unit activity are correlated with high gamma power of the LFPs [20][22], an intriguing possibility is that the high gamma activity that we report in this study is closely related to the multi-unit discharges recorded in animal primary auditory cortex during vocalization. Indeed, it has been found that the high gamma activity can be closely tied to neuronal discharge activity in human auditory cortex when subjects listen to naturalistic stimuli [20], [22].…”
Section: Discussionmentioning
confidence: 74%
“…We focus on the high gamma range, because activity in this range has been shown to reflect multi-unit discharge rates and local field potentials of neuronal ensembles underneath each electrode [20][22]. Furthermore, this signal has been shown to track the envelope of speech-related sounds in the putative core auditory cortex in humans [18].…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy-treated patients revealed more subjective cognitive complaints and a significantly poorer performance in the word fluency professions test. As well, treated patients made more errors during a Flanker task and a Tower of London task, both administered in an fMRI assessment presented in an earlier paper [56]. The authors skillfully compared the anatomical results from this paper to functional assessments, the latter discussed in the fMRI section below.…”
Section: Findings From Imaging Studiesmentioning
confidence: 94%
“…To account for the different press durations of each trial when estimating the perievent firing rate, each press duration was normalized to the criterion duration before firing rate estimation calculations (Mukamel et al, 2011). This made it possible to calculate a reliable perievent firing rate estimate for press durations, even when a session contains many trials with different press durations.…”
Section: Methodsmentioning
confidence: 99%